Physico-chemical aspects of anatase retention during papermaking - Joseph L. Pearson (1973)
A study has been made of the factors which affect anatase retention during papermaking. By using electrophoretic, streaming potential and adsorption techniques a study of the effect of pH, rosin size, aluminium sulphate and various physical parameters on the electrokinetics of the system has been made. Using the Derjaguin–Landau–Verwey and Overbeek theory of colloid interaction it is found that maximum retention of anatase occurs when flocculation of the system is predicted by the above theory. This maximum retention occurs below a pH of 4.0 when the paper 'is made from cellulose fibres and anatase only. On the addition of aluminium sulphate however a high retention is obtained up to a pH of 7 to 9, the limit being dependant on the amount of aluminium sulphate. This increase over the pH range 4 to 7 is attributed to the adsorption of aluminium species on the anatase over this range which causes a large shift in the isoelectric point. A parallel study of the retention of rosin size has been made, and from the results obtained it is proposed that not only are the retention mechanisms of size similar to that of the anatase, but in fact it is the adsorption of one which causes the retention of the other.